A series of 3d–4f heterometallic MOFs: syntheses, structures, optical, and electrochemical properties. Issue 16 (17th September 2018) - Liu, Yukun; He, Guimei; Chen, Yiyu; Tian, Kang; Cao, Feng; Zhang, Chi; Zhu, Wenhua; Wang, Juan
Abstract: A series of heterometallic metal-organic frameworks (MOFs) employing pyridine-2, 6-dicarboxylate and 1, 10-phenanthroline as ligands have been synthesized hydrothermally. In isostructural compounds1 –3 [Ln(pydc)3 Cu2 (phen)4 ]·I·× H2 O (Ln = La (1 ), Nd (2 ), Dy (3 ); x = 6, 5, 5), the metalloligand [Ln(pydc)3 ] assembles with [Cu(phen)2 ] units to construct a dodecanuclear cluster via Cu–O bonds and π–π interactions. The clusters are further stacked into three-dimensional supramolecular frameworks with nano-sized cavities. In [La(Hpydc)(pydc)2 Zn(phen)3 ]·3H2 O (4 ), the metalloligand [Ln(Hpydc)(pydc)2 ] assembles with [Zn(phen)3 ] units to construct a tetranuclear cluster via electrostatic interaction and π–π interaction. This work reveals that the changes of lanthanide metalloligands and the coordination pattern of 3d transition centers would result in significant variation in the final structures. The thermal, optical, and electrochemical properties have been well investigated. Abstract :